Application of the principle of rule of law in the practice of the European court of human rights - Hrubinko, Andrii; Halashyn, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
Taking into account the developments of modern domestic and foreign science, the problems of application the rule of law the European Court of Human Rights principle in practice of the European Court of Human Rights. The theoretical and legal analysis of problems of application the practice by domestic is carried out and ways of solving the problem are proposed.